2016
DOI: 10.1021/acs.jafc.6b03808
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Dietary Resistant Starch Partially Corrected the Growth Pattern Despite Hyperglycemia and Compromised Kidney Function in Streptozotocin-Induced Diabetic Rats

Abstract: We previously demonstrated that feeding of dietary resistant starch (RS) prior to the induction of diabetes delayed the progression of diabetic nephropathy and maintained vitamin D balance in streptozotocin (STZ)-induced type 1 diabetic (T1D) rats. Here, we examined the impact of RS on kidney function and vitamin D homeostasis following STZ injection. Male Sprague-Dawley rats were administered STZ and fed a standard diet containing cornstarch or 20, 10, or 5% RS for 4 weeks. T1D rats fed 10 and 20% RS, but not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…Whilst RS has been shown to reduce albuminuria in the adenine-induced CKD model [11] and the Zucker diabetic fatty rat, an obesity driven model of diabetes [10], a recent study that utilised the STZ model in Sprague-Dawley rats showed that RS had no protective effect on albuminuria [12]. This is consistent with the findings reported here, that in STZ-induced diabetic mice RS supplementation did not alter albuminuria or blood urea levels.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Whilst RS has been shown to reduce albuminuria in the adenine-induced CKD model [11] and the Zucker diabetic fatty rat, an obesity driven model of diabetes [10], a recent study that utilised the STZ model in Sprague-Dawley rats showed that RS had no protective effect on albuminuria [12]. This is consistent with the findings reported here, that in STZ-induced diabetic mice RS supplementation did not alter albuminuria or blood urea levels.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, in the adenine-induced rat model of chronic kidney disease (CKD), supplementation of 59% HAMS diet (Hi-maize 260, equivalent to 27% RS) for three weeks was associated with improvements in creatinine clearance [11]. Conversely however, a study that supplemented a diet containing 55% HAMS (Amylogel, equivalent to 20% RS) for four weeks in male Sprague-Dawley rats with streptozotocin-induced diabetes did not find any renoprotective benefit with RS supplementation [12]. Whilst these results show promise, the concentrations of HAMS used in these studies are likely to be much greater than could be reasonably expected to be consumed by people.…”
Section: Introductionmentioning
confidence: 99%
“…Standard diet consisted of 54.61% nitrogen-free extract (mainly represented by starch and hemicellulose), 5.54% fibers, 19.42% protein, 11.09% water, 2.58% lipids, and 6.76% ash (non-organic mineral matter) (3.9 kcal/g; 4RF21, Mucedola, Italy). The percentage of substrate supplementation to standard chow diet was determined based on published literature: 10% (w/w) I ( Van den Abbeele et al, 2011 ; Pattananandecha et al, 2016 ), 10% (w/w) RS ( Koh et al, 2016 ), and 3% (w/w) CP ( Tian et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…During this study, diabetes was induced in a cohort of healthy rats. Evolution of diabetes might induce other diseases including renal dysfunction (Chen et al, 2017) and malnutrition (Koh, Rowling, Schalinske, Grapentine, & Loo, 2016). However, these conditions were not tested in this study and might have influenced wound healing response.…”
Section: Discussionmentioning
confidence: 99%